Solitude at periphery: lack of partners limits reproduction of the Black Stork (Ciconia nigra) at the margin of the distribution range - Konovalov, Annika; Nellis, Rein; Nellis, Renno; Nurmla, Ain; Sellis, Urmas; Väli, Ülo (Ornis Fennica, 2019)
Understanding the mechanisms forming species’ ranges is a central ecological question, which could be answered by analysing factors limiting peripheral populations. In threatened species, such studies are essential for establishing effective conservation measures across the range. We analysed factors potentially influencing breeding in a declining peripheral population of a long-lived bird, the Black Stork (Ciconia nigra). We assessed reproductive success and the effects of intra- and interspecific competition, as well as predation by recording events at nests by remote cameras (camera traps and a webcam). Productivity of storks was low (1.1 fledglings per occupied nest) compared to the other parts of the range and resulted mainly from the lower proportion of successful nests (37% of occupied nests). The main reason for low breeding success was the occupancy of many nests (35%) by single non-reproductive birds.